Effects of Line of Vision on Posture, Muscle Activity and Sitting Balance During Tooth Preparation - Katsushi Katano; Kazunori Nakajima; Maho Saito; Yoshiaki Kawano; Tomotaka Takeda; Kenichi Fukuda (Elsevier, 2021)
Objectives: Most dentists maintain awkward and restricted postures for prolonged periods that stress the body while providing direct patient care. Information about working posture must be analysed in a more systematic manner to provide a deeper understanding of the relationship between working posture and work-related musculoskeletal disorders (MSD). Therefore, the present study aimed to clarify the effects of different lines of vision during tooth preparation, such as the direct and the mirror view technique, on-body tilt (angle), muscle activity, and sitting balance, which may correlate with the reduction or prevention of MSD. Methods: A mannequin head with a maxillary right first molar embedded in a model was attached to the dental chair headrest. Two different techniques for tooth preparation were selected: direct view and mirror view. Muscle activity, body tilt (angle), and sitting balance were analysed as independent parameters. Results: Different tooth preparation techniques had a distinct influence on body tilt (angle), muscle activity, and sitting balance. The direct view technique resulted in significantly larger values for all parameters, except for the activity of the spinal column erector muscles than the mirror view technique. Conclusion: Based on these results, the direct view technique for tooth preparation, which is used by most dentists in practice, imposes a burden on the lower back, shoulders, and neck of the dentist.